Zasady ujawniania i wyceny wbudowanych instrumentów finansowych - Remlein, Marzena (The Principles of Exposure and Valuation of Built-in Financial Instruments, 2005)
The aim of this paper is to present the principles of exposure and valuation of built-in financial instruments and methods of incorporating them into books of accounts, in accordance with the provisions of the Polish accounting law and solutions adopted by the IAS. The content consists of the following parts: 1. Introduction, 2. Financial instruments in the accounting law, 3. The concept and classification of financial instruments, 4. The principles of exposure of built-in financial instruments, 5. The valuation of built-in financial instruments, 6. Incorporating the built-in financial instruments into books of accounts and the financial statement, 7. Conclusions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1079, s. 271-284